Masque of the Red Death - Griffin, Bethany; Poe, Edgar Allan, 1809-1849. (New York, NY : Greenwillow Books, 2013)
In this twist on Edgar Allen Poe's gothic short story, a wealthy teenage girl who can afford a special mask to protect her from the plague that decimated humanity in the mid-1800s, falls in love, becomes caught up in a conspiracy to overthrow an oppressive government, and faces the threat of a new plague.
Booklist
Publisher's Weekly
School Library Journal
Booklist, May 2012
Bulletin (Center for Children's books), June 2012
Horn Book, May 2012
Keywords: Plague -- Juvenile fiction; Wealth -- Juvenile fiction; Adventure and adventurers -- Fiction; Love -- Fiction; Plague -- Fiction; Wealth -- Fiction; Adventure fiction; Love stories; Plague -- Fiction; Wealth -- Fiction; Adventure fiction; Love stories